A Nursing Informatics Research Agenda for 2008–18: Contextual Influences and Key Components - Bakken, Suzanne (2008)
The context for nursing informatics research has changed significantly since the National Institute of Nursing Research-funded Nursing Informatics Research Agenda was published in 1993 and the Delphi study of nursing informatics research priorities reported a decade ago. The authors focus on three specific aspects of context - genomic health care, shifting research paradigms, and social (Web 2.0) technologies - that must be considered in formulating a nursing informatics research agenda. These influences are illustrated using the significant issue of healthcare associated infections (HAI). A nursing informatics research agenda for 2008–18 must expand users of interest to include interdisciplinary researchers; build upon the knowledge gained in nursing concept representation to address genomic and environmental data; guide the reengineering of nursing practice; harness new technologies to empower patients and their caregivers for collaborative knowledge development; develop user-configurable software approaches that support complex data visualization, analysis, and predictive modeling; facilitate the development of middle-range nursing informatics theories; and encourage innovative evaluation methodologies that attend to human-computer interface factors and organizational context.